Deviant Behaviors of Students in Educational System: A Meta-synthesis Model-Building Theory - Mehdi Mohammaadi; Farzane Deimehkar Haghighi (جامعه شناسی کاربردی, 2024)
Introduction Deviant behavior among adolescents is a complex phenomenon shaped by a variety of individual, familial, peer, and societal influences. Psychological theories, including attachment theory, social control theory, and social learning theory, offer valuable frameworks for analyzing and understanding these behaviors. Previous research has largely concentrated on the impact of family dynamics, peer relationships, and school experiences in influencing adolescent deviance. However, despite significant advancements in this area, a comprehensive understanding of the underlying mechanisms and the interactions among these factors remains elusive. This study aimed to develop a holistic model that clarified the antecedents, processes, and consequences of deviant behavior in adolescents. By deepening our understanding of this issue, we could create and implement more effective prevention and intervention strategies to reduce the prevalence of such behaviors among young people.